Rogues, thieves, and the rule of law : the problem of law enforcement in north-east England, 1718-1800 - Morgan, Gwenda (UCL Press, 1998)
Rogues, Thieves and the Rule of Law"" is a large-scale study of crime, disorder and law enforcement in northern England in the early modern period. London was not the only city where female criminals were common and gangs were feared, nor was it the sole centre of industrial and political agitation. The north was an area of national significance which supplied the capital with its fuel and whose tendency to industrial insurgence commanded the attention of every 18th-century administration.; Arguing that much of the recent work on early modern crime has focused on London and its surrounding cou